Proceedings 2000 ICRA. Millennium Conference. IEEE International Conference on Robotics and Automation. Symposia Proceedings (C
DOI: 10.1109/robot.2000.844846
|View full text |Cite
|
Sign up to set email alerts
|

Emergent structures in modular self-reconfigurable robots

Abstract: We demonstrate how simple local sensing and control rules achieve usefil emergent behaviors in modular self-reconfigurable (metamorphic) robots. Our biologically inspired approach grows structures with the desired functionality even though the final shapes have some unspecified, random variation. By contrast, other self-reconfiguration algorithms require an a-priori exact descriptaon of a target shape for the given task, which may be dificult when a robot operates in uncertain environments. We present and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 15 publications
0
62
0
Order By: Relevance
“…A gradient or virtual hormones could be propagated instead of rule IDs. This would potentially make the morphology formation process more stochastic, thus moving towards the approaches presented in (Bojinov et al 2000;Shen et al 2004). Alternatively, the s-bots could use sensor readings to determine in which direction to open the next connection slot based on local features of the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A gradient or virtual hormones could be propagated instead of rule IDs. This would potentially make the morphology formation process more stochastic, thus moving towards the approaches presented in (Bojinov et al 2000;Shen et al 2004). Alternatively, the s-bots could use sensor readings to determine in which direction to open the next connection slot based on local features of the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Bojinov et al (2000) have shown how a simulated modular robot (Proteo) can selfreconfigure into useful and emergent morphologies when the individual modules use local sensing and local control rules. Some of the practical and theoretical implications of adapting the shape of a self-reconfigurable robot to its environment have been studied by Yu et al (2007) and Yu and Nagpal (2008).…”
Section: Related Workmentioning
confidence: 99%
“…These algorithms may be broadly categorized into gradient-based [4]- [11] and graph-grammar [12]- [15] or shape complex [16] algorithms. Early gradient-based algorithms suffered from either a lack of expressivity [6], or tended to become stuck in state-space minima [4], [5]. Later work by Støy [7]- [9] allowed for the creation of arbitrary shapes, without the danger of getting "stuck" in minima.…”
Section: Related Workmentioning
confidence: 99%
“…Rhombic dodecahedral robots: Yim et al [19], Zhang et al [20] and Bojinov et al [1] present distributed algorithms to reconfigure rhombic dodecahedral modules. These algorithms are probabilistic and require substantial message passing between neighboring modules.…”
Section: A Related Workmentioning
confidence: 99%
“…In these systems, robots achieve locomotion by moving over a substrate composed of one or more other robots. The mechanics of locomotion depend on the hardware and can include module deformation [6], [12], [13] or rigid motion [1], [7], [10], [11] [19], [20].…”
Section: Introductionmentioning
confidence: 99%